The Nutritional Implications of Oral Contraceptives on Women - Maduforo, Aloysius Nwabugo; Yakubu, Tamimu; Nweke, Chizoba P. Okwy; Onoja, Ifeoma Uzoamaka; Okwara, Chinyere C. (Pakistan Journal of Nutrition, 2016)
Oral contraceptives are used by a large proportion of women to prevent pregnancy and also for family planning purposes. This review focused on the effects of oral contraceptives on micronutrient (vitamins and minerals) status of users. Several studies have investigated whether or not women on oral contraceptives need different amounts of some vitamins and minerals. These studies have shown that the key nutrients affected by oral contraceptives include folic acid, vitamins B2, B6, B12, vitamin C, A and E and the minerals: iron, copper, magnesium, sodium, selenium and zinc. The levels of these micronutrients in the blood of women who use oral contraceptives compared to women who do not, have been the focus of most research. Taking appropriate dietary supplements is recommended to be the initial intervention approach by clinicians since several factors such as bioavailability, malabsorption, inadequate consumption, unhealthy lifestyles and pathological conditions can interfere more with the dietary sources of these micronutrients. Review on the food sources of the lacking nutrients and the dietary management of nutritional deficiencies were also documented in this review.